Using Procedure Based on Item Response Theory to Evaluate Classification Consistency Indices in the Practice of Large-Scale Assessment - Zhang, Shanshan; Du, Jiaxuan; Chen, Ping; Xin, Tao; Chen, Fu (Frontiers in Psychology, 2017)
In spite of the growing interest in the methods of evaluating the classification consistency (CC) indices, there is little research on the field of applying these methods in the practice of large-scale educational assessment. In addition, few studies considered the influence of practical factors, for example, the examinee ability distribution, the cut score location and the score scale, on the performance of CC indices. Using the newly developed Lee’s procedure based on the item response theory (IRT), the main purpose of the article is to investigate the performance of CC indices when practical factors are taken into consideration. A simulation study and an empirical study were conducted under comprehensive conditions. Results suggested that with negatively skewed distribution, the CC indices were larger than with other distributions. Interactions occurred between ability distribution, cut score location and score scale. Consequently, Lee’s IRT procedure is reliable to be used in the field of large-scale educational assessment and when reporting the indices it should be treated with caution since testing conditions may vary a lot.